Shear Strength and Microstructure of Intact Loess Subjected to Freeze-Thaw Cycling. (25th August 2021) - Liu, Kuan; Ye, Wanjun; Jing, Hongjun
Abstract : In the Loess Plateau, seasonal freeze and thaw cause great damage to the mechanical behavior and microstructure of soil, which leads to frequent geological disasters during winter and spring. To investigate the influence of freeze-thaw (FT) cycling (FTC) on the shear strength and microstructure of intact loess, triaxial shear, nuclear magnetic resonance, and scanning electron microscope tests were carried out on soil samples after target FT cycles. The results indicate that the FTC has limited changes to the soil stress-strain curve, but has a significant attenuation effect on the peak deviatoric stress. The peak deviatoric stress was attenuated by FTC but changed insignificantly after ten cycles. The cohesive force decays exponentially with the number of FT cycles, while the internal friction angle increases slightly. Moreover, under FTC, the T 2 hydrogen spectra of soil samples showed a multimodal distribution, with the main peak appearing to have two obvious upward shifts that occurred at 6 and 10 FT cycles. Indeed, a depolarization phenomenon related to the directional frequency of soil particles was observed, and the mass fractal dimension of the pore network increased slightly. In an FT environment, the shear strength declines due to accumulated internal microstructural damage. These findings contribute to a better understanding of the response of loess to FTC and provide novel ideas for the prevention of frost damage in loess areas.